Pengembangan E-LKPD Berbasis Problem Solving untuk Meningkatkan Keterampilan Metakognitif Peserta Didik pada Materi Asam Basa: Pengembangan E-LKPD Berbasis Problem Solving untuk Meningkatkan Keterampilan Metakognitif Peserta Didik pada Materi Asam Basa - Adeliani, Afrilia Dwi; Hidayah, Rusly (UNIB Press, 2025)
This study aims to develop problem solving-based e-worksheet to improve students' metacognitive skills on acid-base material. The components of metacognitive skills used are planning, monitoring and evaluation skills. The feasibility of problem solving-based e-worksheet is reviewed from its validity, practicality, and effectiveness. This research refers to the 4D design which consists of four main stages, namely defining (Define), Designing (Design), Developing (Develop) and Disseminating (Disseminate), but in this study it is limited to the third stage, namely Development (Develop). Limited trials were conducted on 32 students of class XI M1 at SMA IPIEMS Surabaya. The research results obtained include (1) The mode score for content and construct validity is 4, which is included in the valid category; (2) students' responses are included in the very good category with a percentage of 97.9%; (3) students' activities and learning implementation are included in the very good category with a percentage of 96.11%. (4) the normality test results show a Sig value of > 0.061 and 0.068, which means greater than the error rate (α) of 0.05, so the data is normally distributed; and (5) the Paired sample t-test results show a Sig value of 0.000, which means less than 0.05 so that H₀ is rejected and Ha is accepted. Thus, there is an increase in students' metacognitive skills after using problem-based e-worksheet.